The rôle of biology, physics and chemistry in human health. - Ramsden, Jeremy J. (Jointly by, Collegium Basilea (Institute of Advanced Study) and Association of Modern Scientific Investigation., 2007)
Health is a perennially dominant preoccupation of man, and must have been so since the earliest days of his existence. One of the most ancient ritualized statements is “To your good health!”, the literal equivalent of which can be found in almost every language (“Zum Wohl!”, “Santé!”, “Egészségére!”, etc.), whenever glasses are raised and a toast is drunk at a social gathering. The Duke of Edinburgh, husband of Queen Elizabeth II of England, attributes his enduring good health to the innumerable such toasts drunk to him, even in absentia, as is the custom at a formal English banquet. Although in Georgia a whole string of toasts is typically drunk,1 the toast to good health is considered to be among the most important; in other countries with a less developed tradition of toasting, it is typically the only one. This preoccupation might, upon first consideration, appear to be superfluous. A living organism is healthy almost by definition—simply because the sick are less likely to survive, and in the long term therefore those prone to sickness are less likely to leave descendants, according to Darwin’s principle. Health should therefore properly be seen as something privative, denoting the absence of ill-health.